The Semantic Faces of The Words of Guiding in The Holy Quran - Allawi, Iyad Saleh; Alwan Iltayif, Muhammad (Journal of Tikrit University for Humanities, 2020)
The Arabic language is one of the world's most extensive semantic languages in comparison with other languages. The word in Arabic has multiple meanings and changeable meanings according to structure. The Holly Qur’an and its structural connotations for words are a broad field for semantic study, and this research, titled: (semantic faces of the guiding words in the Holy Qur’an) deals with changing the meaning of the word guidance in the Holy Qur’an based on the books of interpretation and the lexicographers and hadith books, as we counted twenty-two semantic faces of them, reinforcing the research with evidence and telling scholars from different eras.